2021
DOI: 10.7759/cureus.12519
|View full text |Cite
|
Sign up to set email alerts
|

Percentages of Cases in Operating Rooms of Sufficient Duration to Accommodate a 30-Minute Breast Milk Pumping Session by Anesthesia Residents or Nurse Anesthetists

Abstract: Introduction: Accommodating breast milk pumping sessions is required by US federal statute, but fulfillment is challenging for US anesthesia providers (e.g., anesthesia residents and nurse anesthetists). Considerations of good anesthesia practices (e.g., being present for critical portions of cases, including induction and emergence) create limits on which procedures are suitable for such relief. Our objective was to quantify the minimum percentages of cases for which there could reliably (≥ 95%) be at least 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 24 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…Our university’s Institutional Review Board determined that this project [ 1 , 2 ] does not meet the regulatory definition of human subjects research because the activity was limited to the analysis of de-identified data provided for routine administrative purposes. Three facilities of one large university group practice were studied (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our university’s Institutional Review Board determined that this project [ 1 , 2 ] does not meet the regulatory definition of human subjects research because the activity was limited to the analysis of de-identified data provided for routine administrative purposes. Three facilities of one large university group practice were studied (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The historical period to estimate future surgical times was three years from October 2016 through September 2019 [ 1 , 2 ]. We used every one of the 95,146 cases performed at the university’s surgical suites, with no exclusions, to predict future surgical times [ 1 , 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations